Study on The Measurement of Banks’ Digital Transformation Level Based on Topsis Comprehensive Evaluation Method - Taking The Middle and Lower Yangtze River Region as An Example - Zhang, Yuxuan (Transactions on Economics, Business and Management Research, 2024)
Investigating the digital transformation of banks is essential to fostering regional economic expansion. This serves as the foundation for the bank digital transformation indicators article creates, which includes 15 tertiary indicators and 4 secondary indicators. The bank digital transformation indicators are given indicator weights using the AHP hierarchical analysis method. Finally, utilizing the Topsis complete assessment approach, a comparative study was carried out on the score measurement of banks’ digital transformation development level in the middle and lower portions of the Yangtze River. The indicators of asset size, deposit, and loan ratios, and ROE were found to have bigger weights. The digital transformation scores of banks in Jiangxi Province were determined to be the lowest, while those in Shanghai were the highest. This results in suggestions for bolstering bank data governance, expediting digitization, and developing a forward-looking strategy plan.